Short- and Medium-term Effects of Informal Care Provision on Health - Hendrik Schmitz; Matthias Westphal (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
This paper estimates the effect of informal care provision on female caregiver's health. We use data from the German Socio-economic Panel and assess eff ects up to seven years after care provision. A simulation-based sensitivity analysis scrutinizes the sensitivity of the results with respect to potential deviations from the conditional independence assumption in the regression adjusted matching approach. The results suggest that there is a considerable short-term effect of informal care provision on mental health which fades out over time. Five years after care provision there are no signifi cant effects left. Both short- and medium-term effects on physical health are much smaller and insignificant throughout. – – In diesem Papier wird der Einfluss häuslicher Pflege auf die Gesundheit weiblicher Pflegepersonen mit einem regressions-adjustierten Matchingverfahren untersucht. Wir verwenden Daten des Sozio-ökonomischen Panels und messen Effekte bis zu sieben Jahre nach Pflegetätigkeit. In einer simulationsbasierten Sensitivitätsanalyse wird die Robustheit der Ergebnisse gegenüber potentiellen Abweichungen von der Conditional Independence Annahme beleuchtet. Die Ergebnisse zeigen einen deutlichen Kurzfristeffekt von Pflege auf die mentale Gesundheit, der aber über die Zeit verschwindet. Fünf Jahre nach Pflegetätigkeit liegen keine signifikanten Effekte mehr vor. Sowohl Kurz- als auch Mittelfristeffekte auf die physische Gesundheit sind insgesamt viel kleiner und durchgängig insignifikant.
Keywords: I10; I18; C21; J14; 330; informal care; regression adjusted matching; propensity score matching; mental health; physical health